2022
DOI: 10.3390/bios12121084
|View full text |Cite
|
Sign up to set email alerts
|

A Catechol-Meter Based on Conventional Personal Glucose Meter for Portable Detection of Tyrosinase and Sodium Benzoate

Abstract: In this study, the personal glucose meter (PGM) was first used as a fast and user-friendly meter for analyzing catechol (CA) based on the reduction of the mediator K3[Fe(CN)6] to K4[Fe(CN)6] in the glucose test strip. Then, an easy, low-cost, and convenient PGM-based method for detecting tyrosinase (TYR) activity and sodium benzoate (SBA) was developed on the basis of the TYR-catalyzed reaction. In this method, CA is oxidized to form o-benzoquinone by TYR, thereby reducing the residual amount of CA and the PGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The methods presented in this review article showed great promise with respect to disease diagnosis and drug discovery. Within this context, Tian et al first adopted a personal glucose meter (PGM) as a rapid and practicable tool for the analysis of catechol (CA) based on the reduction of the mediator K 3 [Fe(CN) 6 ] to K 4 [Fe(CN) 6 ] in glucose test strips [ 20 ]. CA could be readily oxidized by TYR to o -benzoquinone, thereby reducing the residual amount of CA and the PGM readout.…”
mentioning
confidence: 99%
“…The methods presented in this review article showed great promise with respect to disease diagnosis and drug discovery. Within this context, Tian et al first adopted a personal glucose meter (PGM) as a rapid and practicable tool for the analysis of catechol (CA) based on the reduction of the mediator K 3 [Fe(CN) 6 ] to K 4 [Fe(CN) 6 ] in glucose test strips [ 20 ]. CA could be readily oxidized by TYR to o -benzoquinone, thereby reducing the residual amount of CA and the PGM readout.…”
mentioning
confidence: 99%